Relationships between food and diseases: What to know to ensure food safety. (November 2020) - Gallo, Monica; Ferrara, Lydia; Calogero, Armando; Montesano, Domenico; Naviglio, Daniele
Graphical abstract: Highlights: Food can be a vehicle for pathogens and therefore potential sources of disease. Microorganisms such as bacteria, viruses and parasites can be responsible for foodborne diseases. Mycotoxins can be present in commonly used foods and pose a serious health threat. The increase in food allergies seems related to a greater intake of non-natural substances. Some foodborne diseases can result from dietary manipulations. Abstract: In recent years, the concept of food has undergone a radical transformation to the point of attributing to foods, in addition to their nutritional and sensorial properties, an important role in maintaining health and psycho-physical well-being and in the prevention of certain diseases. However, foods can hide many pitfalls for human health. There are many critical points in food production processes and they can represent real risks of contamination or of unsafe food production for consumers. Proper conservation, physico-chemical and microbiological stability, cooking methods are fundamental control parameters to ensure the safety of food products. Generally, the development of a food-borne disease is due to specific conditions, such as the virulence of the microorganism present, the microbial load present in the food and the conditions of the host's immune system. Furthermore, the possible presence of other types of contaminants, in addition to microbial ones, can have implications for the health of consumers. Consequently, the rigorous compliance of personnel who work in contact with food during the phases of production, processing, transport and storage with hygienic rules is essential to guarantee food safety and prevent foodborne disease. So, in this review, major issues are addressed such as reviewing the major food-related causes of disease. From this point of view, the relevant microorganisms involved in food contamination (bacteria, viruses, parasites, fungi and mycotoxins), are taken into account. In addition, potentially allergenic foods or foods most commonly associated with food intolerance, are also considered. Many adverse reactions of the body towards foods are caused by the treatments to which they are subjected in order to maintain unchanged organoleptic characteristics as long as possible over time. This is also a critical point for food contamination that is considered in this review. A section is reserved to food additives potentially capable of causing disorders to the human body. In addition to biological contamination, the important issues represented by chemical contamination caused by pesticides, heavy metals, contaminants produced involuntarily are also considered. In conclusion, this review highlights that to protect consumers from food-borne diseases, an integrated approach to food safety must be adopted which affects the entire food chain, from farm to fork.